2021
DOI: 10.5603/fhc.a2021.0003
|View full text |Cite
|
Sign up to set email alerts
|

miR-140-5p inhibits the proliferation, migration and invasion of vascular smooth muscle cells by suppressing the expression of NCKAP1

Abstract: Introduction. The occurrence of aortic dissection is related to the proliferation and metastasis of vascular smooth muscle cells. In our present study, we found that the expression of miR-140-5p was inhibited in the wall of abdominal aorta of aortic dissection patients. However, the mechanism of miR-140-5p in the development of aortic dissection is unclear. Material and methods. We detected the expression of miR-140-5p and NCK Associated Protein 1 (NCKAP1) in blood vessel of aortic dissection patients and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A study revealed that miR-140-5p-mediated inhibition of NCKAP1 leads to a decrease in the ability of cells to proliferate, migrate, and invade. This could be due to the suppression of NCKAP1 affecting the cell's skeletal structure and signal transduction pathways, thus in uencing the cell's ability to proliferate, migrate, and invade [15]. Additionally, NCKAP1 is closely associated with several molecular pathways (the in ammatory promotion pathway, HLA pathway, cell lytic activity, cell apoptosis pathway, type II IFN response, complement and coagulation cascade responses) and several cytokines (PDGFRB, IL-10, IFNG, and TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that miR-140-5p-mediated inhibition of NCKAP1 leads to a decrease in the ability of cells to proliferate, migrate, and invade. This could be due to the suppression of NCKAP1 affecting the cell's skeletal structure and signal transduction pathways, thus in uencing the cell's ability to proliferate, migrate, and invade [15]. Additionally, NCKAP1 is closely associated with several molecular pathways (the in ammatory promotion pathway, HLA pathway, cell lytic activity, cell apoptosis pathway, type II IFN response, complement and coagulation cascade responses) and several cytokines (PDGFRB, IL-10, IFNG, and TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shed light on the significance of miR-188-5p in AAA progression, demonstrating its upregulation and its impact on elastin degradation, VSMC depletion, and mural angiogenesis inhibition [ 34 ]. Similarly, miR-140-5p suppression has been observed in acute aortic dissection (AAD) patients, correlating with upregulated NCKAP1 levels, influencing VSMC proliferation, migration, and invasion [ 35 ]. Deng et al, investigated the role of miR-140/BCL2L2 axis on the formation of IAs.…”
Section: Discussionmentioning
confidence: 99%
“…Biological activities of miR‐140 and miR‐200 in Schwann cells remain largely undetermined although an earlier study demonstrates that miR‐140 directly interacts with myelin transcription factor Egr2 (Krox‐20) and suppresses Schwann cell myelination (Viader et al, 2011). Actually, miR‐140 has been identified as a migration suppressor in many cell types, including macrophages, vascular smooth muscle cells, breast cancer cells, and hepatocellular carcinoma cells (Dou et al, 2021; Li et al, 2021; Ma et al, 2021; Qiao et al, 2022). By restraining the EMT process, miR‐140 hinders cell migration and invasion (Guo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, (Viader et al, 2011). Actually, miR-140 has been identified as a migration suppressor in many cell types, including macrophages, vascular smooth muscle cells, breast cancer cells, and hepatocellular carcinoma cells (Dou et al, 2021;Li et al, 2021;Ma et al, 2021;Qiao et al, 2022). By restraining the EMT process, miR-140 hinders cell migration and invasion (Guo et al, 2020).…”
Section: Enhanced Migration Capacity Of Drg Schwann Cells Indicates Thatmentioning
confidence: 99%